(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
The presence of organizations in people’s lives can help and make it easier for people to meet their needs. BLK Pesantren Community is an institution formed by the government so that Pesantren becomes a community that can economically empower the surrounding community. Because of that, the management of an institution becomes a necessity so that the goals can be achieved. This paper examines the implementation of the management functions of the Islamic Boarding School Community BLK in Blitar City, namely; Al-Muhsin Community BLK, As-Sunnah An-Nabawiyah Community BLK, and Bustanul Muta’alimin Community BLK. Data collection was carried out through interviews with the managers of the Islamic Boarding School Community BLK, the students, and the surrounding community. This research uses a qualitative descriptive approach. The results showed that the application of the management function of the BLKK-P management in Blitar City using the POAC management function theory was quite optimal. The Islamic Boarding School Community BLK has carried out four steps in the management function, namely; planning, organizing, actuating, and controlling.